Implementation of Sustainable Geotourism in Teuweul Honeybee Farming MSMEs in Margawindu Sumedang District - Irena Novarlia; Rifqi Asy'ari; Dally Nur Arif; Gilang Pratama Putra (Unram Journal of Community Service, 2025)
Margawindu Village in Sumedang Regency possesses considerable geotourism potential along with a locally cultivated honeybee product known as Teuweul honey. However, this potential has not yet been optimally integrated into the development of sustainable educational tourism. This community service program aims to implement sustainable geotourism by empowering local MSMEs engaged in Teuweul honey beekeeping through a participatory and community-based tourism approach. The method involved field observations, focus group discussions, thematic training, mentoring, and participatory evaluation followed by strategic recommendations. The results indicated a significant increase in community capacity in terms of environmental conservation and tourism interpretation, the rebranding of Teuweul honey with strong local identity, and the development of an educational tour package titled “From Hive to Nature” that combines ecological, economic, and educational values. Despite existing challenges such as infrastructure limitations and the need for digital marketing skills, the program successfully laid the foundation for an inclusive and locally driven sustainable geotourism model. Continued cross-sector collaboration and stakeholder engagement are essential to ensure the program’s long-term sustainability.